Effect of physical activity on severity of primary angle closure glaucoma - Chong Seong, Niven Teh (Ther Adv Ophthalmol, 2019)
OBJECTIVE: To determine the association between physical activity and severity of primary angle closure glaucoma in Malay patients. METHODS: A cross-sectional study was conducted involving 150 primary angle closure glaucoma patients between April 2014 and August 2016. Using the International Physical Activity Questionnaire, the physical activity status was assessed and divided into three categories: mild, moderate and heavy physical activity. The duration of physical activity and corresponding minimum energy requirements were calculated. Ocular examination was performed including Humphrey visual field 24-2 analysis assessment. Based on two consecutive reliable Humphrey visual fields, the severity of glaucoma was scored according to modified Advanced Glaucoma Intervention Study and classified as mild (0–5), moderate (6–11) and severe (12–20). Association between physical activity and Advanced Glaucoma Intervention Study score was determined with multiple linear regression analysis. RESULTS: A total of 150 Malay patients with primary angle closure glaucoma were included (50 patients with mild, 50 with moderate and 50 with severe glaucoma). Physical activity showed inverse association with the severity of primary angle closure glaucoma. After calculating adjustments for age, sex, duration of glaucoma, body mass index, systemic co-morbidities, family history of glaucoma, myopia and educational status [adjusted b –3.41, 95% confidence interval (–5.23, –1.59), p < 0.001], there was also an inverse relationship with Advanced Glaucoma Intervention Study score. Every increase in physical activity level reduces the Advanced Glaucoma Intervention Study score by 3.4 point. CONCLUSION: Physical activity is the potential modifiable risk factor in reducing the severity of glaucoma among primary angle closure glaucoma patients. However, there is possibility of the severity of glaucoma restricted the physical activity of primary angle closure glaucoma patients.